Selective patterning of out-of-plane piezoelectricity in MoTe2 via focused ion beam. (January 2021) - Seol, Daehee; Kim, Songkil; Jang, Woo-Sung; Jin, Yeongrok; Kang, Seunghun; Kim, Sera; Won, Dongyeun; Lee, Chanwoo; Kim, Young-Min; Lee, Jaekwang; Yang, Heejun; Jeong, Mun Seok; et al.
Abstract: Two-dimensional transition-metal dichalcogenides (TMDs) have a strain-sensitive nature and can only exhibit in-plane piezoelectricity, owing to their in-plane inversion symmetry breaking, which limits their practical applications for vertical stimulations. In this study, we demonstrated the capability of focused ion beams to create out-of-plane piezoelectricity on multi-layered MoTe2 . We utilized a focused helium ion beam to selectively pattern the out-of-plane piezoelectricity via defect engineering in a layered MoTe2 flake. The generated out-of-plane piezoelectricity in the desired area was quantitatively examined using atomic force microscopy, and ion beam irradiation-induced defect formation that gave rise to inversion symmetry breaking was confirmed. These results indicated that the out-of-plane piezoelectricity can be selectively patterned through a focused helium ion beam, and it is expected that this approach can also be applied to other classes of TMDs and can expand the application fields of TMD-based devices. Graphical Abstract: ga1 Highlights: Selective patterning of out-of-plane piezoelectricity in 2D TMDs. Generation/improvement of piezoelectricity using ion beam unlike usual reports on the ion beam irradiation. Atomic-scale inversion symmetry breaking via local defect formation.